ACCRUAL DAN CASH FLOW OPERATING, PENGARUHNYA TERHADAP EXPECTED RETURN SAHAM - Dellania Alifia Permata; Sofie Sofie (Jurnal Akuntansi Trisakti, 2015)
This study aims to examine the effect of accrual and cash flow from operating for stock return expectation. It describes whether the information on accrual and cash flow from operating can be considered in assessing stock expected return. The data used in this study are secondary data taken from companies financial reports, Jakarta Composite Stock Price Index (IHSG), Individual Stock Price Index (IHSI), and Monthly Interest Rate (SBI).This study uses purposive sampling methods with six companies as sample from JII (Jakarta Islamic Index) for the period 2007-2013. Hypothesis testing uses panel regression with t test and F test. The result shows that accrual has a significant influence on stock expected return. Cash flow from operating also has a significant influence on stock expected return. Together, accrual and cash flow from operating, have significant influence stock expected return. Therefore it can be concluded that the information on accrual and cash flow from operating may benefit for investor to measure stock expected return.